1995
DOI: 10.1055/s-0038-1653730
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Protein C Deficiency in the Healthy Population

Abstract: SummaryReported prevalence rates for protein C (PC) deficiency in the population at large have varied widely. The differences presumably reflect the existence of an apparently high number of clinically recessive forms of the deficiency. In an attempt to document more precisely the prevalence of PC deficiency in the healthy population we have measured PC activity in just under 10,000 blood donors in the West of Scotland. After repeat testing of donors with low results and then further observation and selection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
115
1
8

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(132 citation statements)
references
References 35 publications
7
115
1
8
Order By: Relevance
“…Found here in only 1 VV patient. Previous studies have produced conflicting results 2,15,19,20 : one group found a reduction in PC activity in 25% of patients with LDS and CVU; 20 but another found no difference in PC activity in CVU cases vs controls. 15 Yasim et al found no difference in PC activity in patients with VV compared with controls.…”
Section: Resultsmentioning
confidence: 98%
“…Found here in only 1 VV patient. Previous studies have produced conflicting results 2,15,19,20 : one group found a reduction in PC activity in 25% of patients with LDS and CVU; 20 but another found no difference in PC activity in CVU cases vs controls. 15 Yasim et al found no difference in PC activity in patients with VV compared with controls.…”
Section: Resultsmentioning
confidence: 98%
“…36 The population frequencies of natural anticoagulant deficiency in Western ethnic populations have been described as 0.2-0.45% for PC deficiency, 0.03-1.3% for PS deficiency, and 0.02-0.25% for AT deficiency. 9,[37][38][39][40][41][42] The differences in the methodological strategy used to screen for and confirm the deficiency (e.g., type/frequency of tests, family study, and cutoffs) could also have affected the figures. In particular, earlier studies were based only on coagulation tests, while recent studies tend to involve molecular genetic tests to confirm the hereditary nature of the deficiency.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…The prevalence of heterozygosity for protein C deficiency in a healthy general population has been estimated to be between 1 in 200 and 1 in 500; this was established in two large studies of more than 15,000 blood donors. 293,294 The estimated prevalence varied because molecular confirmation of protein C deficiency was not possible in all patients and also because the investigators corrected for the possibility of missed cases of protein C deficiency. In unselected patients with venous thromboembolism, the frequency of protein C deficiency or protein S deficiency is approximately 8%.…”
Section: O Apl and The Protein C Pathwaymentioning
confidence: 99%